Manufacturing Convergence of ASEAN: Too Good to Be True? - Dayang Affizzah, Awang Marikan; Mohd Khairul Hisyam, Hassan; Haslan, B. Ottot (HRMARS, 2020)
Manufacturing sector was one of the main drivers of economic growth at ASEAN and it is expected to expand. Although ASEAN is said to be the monetary area with various types of financial improvements and experiencing financial development, majority of the ASEAN countries are classified as a lower centre wage nation. The study uses the non-linear time varying factor approach on finding structural convergence of value added of manufacturing sectors in ASEAN. Alternatively, if the result shows there are convergence among the country, it could be an indicator of possible deeper economic integration and perhaps feasibility of monetary union. Countries that converges with other countries show that the ability of its to catch up with the higher one despite having different magnitude to converge. As stated in the ASEAN Economic Community (AEC), as a member the country must have the equitable of its economic growth and full integrated region in the global economic. The results indicate that there is no structural convergence in manufacturing sector in ASEAN, however, there are subgroup that converges to three club convergence with core group consist of Philippines and Singapore. The study concludes that manufacturing sector in ASEAN experiences strong similarity in its manufacturing sector and better prospect for convergence in the